2004
DOI: 10.1038/sj.bjc.6601424
|View full text |Cite
|
Sign up to set email alerts
|

Germline truncating mutations in both MSH2 and BRCA2 in a single kindred

Abstract: There has been interest in the literature in the possible existence of a gene that predisposes to both breast cancer (BC) and colorectal cancer (CRC). We describe the detailed characterisation of one kindred, MON1080, with 10 cases of BC or CRC invasive cancer among 26 first-, second-or third-degree relatives. Linkage analysis suggested that a mutation was present in BRCA2. DNA sequencing from III: 22 (diagnosed with lobular BC) identified a BRCA2 exon 3 542G4T (L105X) mutation. Her sister (III: 25) had BC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 25 publications
0
22
1
1
Order By: Relevance
“…Except for the deletion previously described by Stella et al, 5 the other exon 8 deletions found in our families are different from those previously characterized and reported 4,7,25 in the LOVD (Leiden Open Variation Database) database.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Except for the deletion previously described by Stella et al, 5 the other exon 8 deletions found in our families are different from those previously characterized and reported 4,7,25 in the LOVD (Leiden Open Variation Database) database.…”
Section: Discussioncontrasting
confidence: 51%
“…[3][4][5][6][7][8] In this paper we describe the characterization of five different MSH2 exon 8 deletions identified in 13 unrelated Italian families with Lynch syndrome. Interestingly, 10 of the families carrying exon 8 deletions were of Sardinian origin, although the large majority of the probands with MSH2 mutations in our series of families did not have a Sardinian origin.…”
Section: Introductionmentioning
confidence: 99%
“…The role of genomic rearrangements in the etiology of HNPCC has been under-investigated, due to the lack of technically simple and reliable approaches for detecting this type of mutation. Recently, with the development of PCR-based semi-quantitative approaches for detecting gene dosage, it has become apparent that a substantial proportion of HNPCC cases are associated with germ-line genomic rearrangements in the MMR genes, mainly MLH1and MSH2 (Papadopoulos et al, 1994;Nystrom-Lahti et al, 1995;Mauillon et al, 1996;Wijnen et al, 1998;Charbonnier et al, 2000;Charbonnier et al, 2002;Gille et al, 2002;Viel et al, 2002;Wang et al, 2002;Nakagawa et al, 2003;Plaschke et al, 2003;Pyatt et al, 2003;Taylor et al, 2003;Wang et al, 2003;Di Fiore et al, 2004;Miyaki et al, 2004;Thiffault et al, 2004;Casey et al, 2005). A germ-line genomic deletion in HNPCC was first identified as a founder mutation at MLH1 among the Finnish population (Nystrom-Lahti et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, this condition has been referred to as the constitutional mismatch repair deficiency syndrome (CMMR-D) (Wimmer and Etzler, 2008). The majority of reported Lynch syndrome-causing mutations have been point mutations; however, increasingly, gross genomic rearrangements have been observed due to the widespread use of reliable methods to detect them (Papadopoulos et al, 1994;Nystrom-Lahti et al, 1995;Mauillon et al, 1996;Wijnen et al, 1998;Charbonnier et al, 2000;Charbonnier et al, 2002;Gille et al, 2002;Viel et al, 2002;Wang et al, 2002;Nakagawa et al, 2003;Plaschke et al, 2003;Pyatt et al, 2003;Taylor et al, 2003;Wang et al, 2003;Di Fiore et al, 2004;Miyaki et al, 2004;Thiffault et al, 2004;Casey et al, 2005;van der Klift et al, 2005;Li et al, 2006). A germline genomic deletion in Lynch syndrome was first identified as a founder mutation in MLH1 within the Finnish population (Nystrom-Lahti et al, 1995).…”
Section: Introductionmentioning
confidence: 99%